Stimulator of Interferon Genes-Associated Vasculopathy With Onset in Infancy: A Systematic Review of Case Reports - Dai, YunFan; Liu, XiuYun; Zhao, ZhiPeng; He, JianXin; Yin, QingQin (Frontiers in Pediatrics, 2020)
Objective: Summarize and analyze the manifestations of STING-associated vasculopathy with onset in infancy (SAVI) for further understanding of the disease. Methods: Since SAVI was first reported in 2014, a systematic literature search was performed from January 1st, 2014 till February 1st, 2020, using PubMed, OVID, CNKI and WanFang. It included all the literatures containing comparatively complete clinical data. SPSS 20.0 was adopted to analyze the difference of onset-age, severity of skin and respiratory symptoms between p.N154S and p.V155M. Results: Total 25 effective papers were eventually included and 51 individuals were involved, of whom 17 were familiar inherited. It included 27 males, 24 females and 8 fatal cases were described. Total 10 mutation sites have been reported till now and p.V155M was the most common one. SAVI was an early-onset disease with a median onset-age of 3 months after birth. Skin-lesion was the most common symptom of SAVI since 94.1% (48/51) cases suffered skin damage, in which 19 of 25 cases revealed vasculopathy by skin biopsy. 68.6% (35/51) of the patients had lung involvements while only 22.2% (4/18) patients who performed lung biopsy showing vasculopathy. Nineteen of 20 patients had immunoglobulin increase, mainly on IgG. 45.1% (23/51) of the ANA results showed low-titer or transient positive. Total 18 patients were treated with JAK-blockers, 6 of them relapsed and 2 died of acute respiratory failure caused by viral infection. Compared with p.V155M, the onset-age of p.N154S is younger(P=0.002), and the skin-lesions are severer(P＜0.001). Conclusion: SAVI is an early-onset disease with lesions on skin and pulmonary. The clinical phenotype varies with different genotypes. The therapeutic effect of JAK inhibitors is unsatisfactory.